Domestic cooking in Brazilian dietary guidelines and its interfaces with food and nutrition public policies and with Nutrition education training/A culinaria domestica nos guias alimentares brasileiros e suas interfaces com as politicas publicas de alimentacao e nutricao e com a formacao em Nutricao - Martins, Carla Adriano; de Castro, Ines Rugani Ribeiro; Maldonado, Luciana Azevedo; Farias, Silvia Cristina; de Oliveira, Mariana Fernandes Brito (Demetra: Alimentação, Nutrição e Saúde, 2025)
Domestic cooking, once historically overlooked, has gained recognition over the past two decades as a key element in promoting Adequate and Healthy Eating (PAHE) and Food and Nutrition Education (FNE) initiatives in Brazil. This essay reflects on how cooking is approached in the Brazilian Dietary Guidelines, exploring its connections with food and nutrition public policies and Nutrition education training. Drawing on the concept of domestic cooking and related frameworks, an expanded and critical approach to this topic can be observed in the current Guidelines, which offer both reflective elements and practical guidelines for strengthening this practice in daily life. In the realm of public policies, while there have been advances in integrating cooking into PAHE and FNE, there is still a need to expand actions that promote critical thinking and autonomy. Policies must also support cooking practices across diverse households and family structures, addressing the obstacles and challenges highlighted in the Guidelines. In Nutrition training, the discussion about cooking is predominant in subjects such as Dietetic Technique and FNE. It is necessary to expand this focus to better meet the Guidelines' recommendations and promote training that is more aligned with the realities of families, from an inclusive and reality-sensitive perspective, intending to overcome challenges such as race, gender and class inequalities. The expanded approach to cooking in the Guidelines represents an important milestone for strengthening this theme in educational actions and in structural public policies, as well as in Nutrition training. Keywords: Food and Nutrition Education. Food and Nutrition Programs and Policies. Professional Training. Dietetic Technique. Embora historicamente negligenciada, a culinaria domestica tem sido valorizada como elemento estruturante da Promocao da Alimentacao Adequada e Saudavel (PAAS) e de acoes de Educacao Alimentar e Nutricional (EAN) nas duas ultimas decadas no Brasil. Este ensaio objetivou refletir sobre como a culinaria e abordada nos Guias Alimentares brasileiros (Guias) e suas interfaces com as politicas publicas de alimentacao e nutricao e com a formacao em Nutricao. Partindo do conceito de culinaria domestica e outros relacionados, observa-se uma abordagem ampliada e critica sobre este tema nos Guias vigentes, que incluem elementos reflexivos e orientacoes objetivas sobre como fortalecer essa pratica no cotidiano. No ambito das politicas publicas, ainda que sejam registrados avancos na abordagem sobre culinaria em acoes de PAAS e EAN, e necessario ampliar as abordagens que incentivam o senso critico e a autonomia. Tambem sao necessarias politicas publicas para apoiar a pratica da culinaria frente a diversidade de domicilios e arranjos familiares, enfrentando os obstaculos e desafios apontados nos Guias. Na formacao em Nutricao, a discussao sobre culinaria e predominante em disciplinas como Tecnica Dietetica e EAN. E necessario expandir esse enfoque para melhor atender as recomendacoes dos Guias e promover uma formacao mais alinhada as realidades das familias, numa perspectiva inclusiva e sensivel a realidade, com vistas a superar desafios como desigualdades de raca, genero e classe. A abordagem ampliada sobre culinaria nos Guias representa um importante marco para o fortalecimento dessa tematica em acoes educativas e em politicas publicas estruturantes, bem como na formacao em Nutricao. Palavras-chave: Educacao Alimentar e Nutricional. Programas e Politicas de Nutricao e Alimentacao. Capacitacao Profissional. Tecnica Dietetica.